2020
DOI: 10.1109/jsen.2020.2979191
|View full text |Cite
|
Sign up to set email alerts
|

Improving Heart Rate Estimation on Consumer Grade Wrist-Worn Device Using Post-Calibration Approach

Abstract: The technological advancement in wireless health monitoring allows the development of light-weight wrist-worn wearable devices to be equipped with different sensors. Although the equipped photoplethysmography (PPG) sensors can measure the changes in the blood volume directly through the contact with skin, the motion artifact (MA) is possible to occur during an intense exercise. In this study, we attempted to perform heart rate (HR) estimation by proposing a post-calibration approach during the three possible s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Signal quality assessment was found to be the most neglected of the methodological aspects contemplated in the risk of bias assessment. Noise and artifacts arising from several sources have an influence on data quality and wearable systems are particularly susceptible to motion artifacts (Mihajlovic et al, 2015 ; Boudreaux et al, 2018 ; Choksatchawathi et al, 2020 ). While these facts are well known, only few studies ( n = 8) identified low-quality signal segments with the purpose of excluding those segments from further analysis or reconstructing them.…”
Section: Resultsmentioning
confidence: 99%
“…Signal quality assessment was found to be the most neglected of the methodological aspects contemplated in the risk of bias assessment. Noise and artifacts arising from several sources have an influence on data quality and wearable systems are particularly susceptible to motion artifacts (Mihajlovic et al, 2015 ; Boudreaux et al, 2018 ; Choksatchawathi et al, 2020 ). While these facts are well known, only few studies ( n = 8) identified low-quality signal segments with the purpose of excluding those segments from further analysis or reconstructing them.…”
Section: Resultsmentioning
confidence: 99%
“…We have reviewed the accuracy of the previous generation smartwatches of these vendors; the accuracy of Apple Watch is the best compared to the other smartwatches, and, surprisingly, better than Empatica E4 [20], [150]. Additionally, Fitbit's and Samsung's smartwatch are comparable to Empatica E4 during the resting state [20], [150], [151]. Considering that all vendors upgrade their PPG technology in the new model smartwatches, higher PPG accuracy can be anticipated, although it has yet to be clarified.…”
Section: Discussion On Smartwatch Candidates For Mental Health Monmentioning
confidence: 99%
“…Digital devices, especially mobile or wearable devices, are increasingly capable of capturing various sources of real-time behavioral, physiological, and psychosocial data in a precise and confidential manner [13]- [15]. Examples of these technologies include smartphones [16]- [18] and smartwatches [19], [20]. Interestingly, how we use these technologies to improve mental well-being or mitigate mental illness in terms of emerging uncertainties is opened to discussion.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous sensor measurement of heart rate also offered redundant information that provided a robust dataset to work with. There is a growing body of literature that shows mechanisms for improvement of heart rate datasets based on machine learning [27] and denoising algorithms [28]. We plan to use such algorithms in a larger study to improve the quality of the heart rate data.…”
Section: B Wearable Sensor Datamentioning
confidence: 99%